Which expression is equivalent to 17x − 8x + 2 and why?

2 − 9x, because (17x − 8x) + 2 = −9x + 2 = 2 − 9x
2 + 9x, because (17x − 8x) + 2 = 9x + 2 = 2 + 9x
11x, because 17x − 8x + 2 = 9x + 2 = 11x
7x, because 17x − 8x + 2 = 17x − 10x = 7x

Respuesta :

Answer:

2 + 9x, because (17x − 8x) + 2 = 9x + 2 = 2 + 9x

Step-by-step explanation:

17x - 8x + 2 = (17x - 8x) +2         Combine like terms.

                   = 9x + 2

Like terms have same variable of same powers.

Answer:

2 + 9x, because (17x − 8x) + 2 = 9x + 2 = 2 + 9x

Step-by-step explanation:

17x - 8x + 2 = (17x - 8x) +2         

Combine like terms.                  

 = 9x + 2 Like terms have same variable of same powers.

Still stuck? Get 1-on-1 help from an expert tutor now.e3radg8 and 3 more users found this answer helpful

ACCESS MORE